THE EFFECT OF EXTENSIVE READING STRATEGY IN IMPROVING VOCABULARY MASTERY AT THE TENTH GRADES NURSING STUDENTS OF SMK KESEHATAN KALTARA TARAKAN - Maghfirotin, Maghfirotin; Ridwan, Ridwan (Universitas Borneo Tarakan, 2021)
The purpose of this study was to determine whether there is a significant difference inimproving the vocabulary of students who are taught using the Extensive Readingstrategy and those taught using the Intensive Reading strategy in the tenth grade ofSMK Kesehatan Kaltara Tarakan. This research method is Quasi-experimental.Samples were selected using the purposive sampling technique. There are two classessampled in this study. The treatment for the experimental class was taught using theExtensive Reading Strategy and the control class using the Intensive Reading Strategy.The research instrument was a multiple-choice written test. The data analyzed werethe pre-test and post-test from the experimental and control classes. In analyzing thedata, researchers used an independent sample T-test at SPSS 23.0. The results showedthat there were differences in the scores of students from the experimental class andthe control class. This is evidenced by the results of the student's average score. Thetest results before being given the treatment (pre-test) of the experimental classobtained an average score of 40.00 and the control class obtained 51.11. Whereas forthe posttest results, the experimental class with a mean score of 69.81, and the posttestresults for the control class with a mean score of 64.26. This can be seen from the twoclasses getting a higher increase after giving a treatment by using extensive readingand intensive reading strategies. The results of the independent sample T-test betweenthe posttest in the experimental class and the control class were (t-score = 2.559) (ttable=2.007)withavalueof0.13.Basedontheexplanationabove,theresultsofthedataanalysis prove that there is a significant difference between students who aretaught using the Extensive Reading strategy and students who are taught using theIntensive Reading strategy in increasing student vocabulary. Ha is accepted when thet-score is higher than the t-table, while Ho is rejected.